2016
DOI: 10.1021/acs.langmuir.5b04038
|View full text |Cite
|
Sign up to set email alerts
|

Thrombin-Responsive Gated Silica Mesoporous Nanoparticles As Coagulation Regulators

Abstract: The possibility of achieving sophisticated actions in complex biological environments using gated nanoparticles is an exciting prospect with much potential. We herein describe new gated mesoporous silica nanoparticles (MSN) loaded with an anticoagulant drug and capped with a peptide containing a thrombin-specific cleavage site. When the coagulation cascade was triggered, active thrombin degraded the capping peptidic sequence and induced the release of anticoagulant drugs to delay the clotting process. The thro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 30 publications
0
18
0
Order By: Relevance
“…The results demonstrated that the release of drug was highly specific to the presence of thrombin. Thrombin results in the hydrolysis of the capping peptide releasing the drug [ 220 ].…”
Section: Applications Of Msns In Drug Deliverymentioning
confidence: 99%
“…The results demonstrated that the release of drug was highly specific to the presence of thrombin. Thrombin results in the hydrolysis of the capping peptide releasing the drug [ 220 ].…”
Section: Applications Of Msns In Drug Deliverymentioning
confidence: 99%
“…Enzyme-responsive nanocarriers can also be applied to regulate coagulation locally. For this purpose, Bhat et al developed a thrombin-responsive mesoporous silica nanoparticle (MSN) that is loaded with an anticoagulant drug and capped with a peptide containing a thrombin-specific cleavage site [137]. When the coagulation cascade is triggered, active thrombin can degrade the capping peptide sequence on the nanocarrier and release the anticoagulant locally [137].…”
Section: Enzyme-responsive Nanocarriersmentioning
confidence: 99%
“…Moreover, the pore‐blockers should respond to appropriate external or internal triggers to close or open the well‐defined pores, causing on‐demand intelligent cargo delivery . Various porekeepers including polymers (e.g., polymer poly(2‐vinylpyridine) (PVP), poly(N‐succinimidyl acrylate), poly(2‐dimethylaminoethyl methacrylate), poly(acrylic acid) brush), host–guest assemblies (e.g., Cyclodextrins, cucurbit,uril, pillararenes), inorganic nanomaterials (e.g., Au NPs, quantum dots, Ag NPs, cerium oxide NPs, manganese oxide NPs, and reduced graphene), and biomacromolecules (e.g., peptides, nucleic acids, saccharides, and proteins) have been employed under certain internal or external stimuli, such as pH, temperature, light, redox potential, ultrasound, small molecules, biomolecules, and or a combination of these stimuli, to achieve controllable DDSs based on mesoporous silica nanoparticles (MSNs) …”
Section: Mesoporous Silica Nanostructuresmentioning
confidence: 99%